2018
DOI: 10.30957/viabel.v11i1.229
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH JARAK TANAM DAN MULSA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TOMAT (Lycopersicon esculentum Mill) PADA MUSIM PENGHUJAN

Abstract: This research aims 1) To determine the effect of interaction of different plant spacing and the provision of mulch to growth and yield of tomato plants. 2) To know the different spacing affect the growth and yield of tomato plants. 3) To know the use of mulch type effect on growth and yield of tomato plants. This research was conducted by using Randomized Block Design in Factorial (RAK) with 2 factors, first factor is plant spacing (J) consisting of 3 levels ie 40x30 cm (J1), 40x50 cm (J2), 40x70 cm (J3) . The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It produces auxin in the form of IAA on the surface and tips of plant roots that can stimulate root elongation, initiation of secondary roots, formation of root fibers, and increase root response in plants to increase the role of roots in the absorption of nutrients and water from the soil [8]. Also, the effectiveness of its application on red onion is proven by [9] research that showed its application with a dose of 10 grams/hole, showed the best results on observations of plant height, wet, and dry weight. Compost is one of the plant-derived organic fertilizers that acts as a source of nutrition for plants and can also improve the physical, chemical and biological properties of soil, so innovation in using compost is needed [10].…”
Section: Introductionmentioning
confidence: 99%
“…It produces auxin in the form of IAA on the surface and tips of plant roots that can stimulate root elongation, initiation of secondary roots, formation of root fibers, and increase root response in plants to increase the role of roots in the absorption of nutrients and water from the soil [8]. Also, the effectiveness of its application on red onion is proven by [9] research that showed its application with a dose of 10 grams/hole, showed the best results on observations of plant height, wet, and dry weight. Compost is one of the plant-derived organic fertilizers that acts as a source of nutrition for plants and can also improve the physical, chemical and biological properties of soil, so innovation in using compost is needed [10].…”
Section: Introductionmentioning
confidence: 99%